(untitled) (Olhar de Professor, 2020)
The article analyzes a proposal for education in Goiás inspired by charter schools. The charter model, created in the United States of America, takes on different designs, with private management with public funding as common characteristics. Brazil, for decades, has lived with similar privatization policies, however, recently the pro-charter movement has gained strength, presenting the model as an innovator and an example to be adopted. The Goiás proposal presents itself as capable of improving IDEB by reducing bureaucratization and privatization of management, so the objective of the article is to analyze the role of external evaluation in the program. External evaluation has been an important pillar in recent educational public policies. More than evaluating educational networks to support the formulation of policies, the result indicators are strategic tools of the discourse that relate quality of education to the results of exams. In the case of management contracts, the proficiency indexes become contractual clauses, deepen accountability and serve as a justification for the adoption of the program. The main question that led the research path was: in what ways can the association between external evaluation and management contracts contribute to deepening the accountability of schools for their results? Based on the question, a documentary analysis of the notices and draft contracts was carried out, which point out that the program could represent a deepening of accountability through external evaluation, with school management and teaching work more oriented to results. Key words: Charter school; Public and private in education; External evaluation; Social organizations and education; accountability.